Modeling of adsorption kinetic and equilibrium isotherms of hydrogen sulfide onto hydrogel biochar adsorbent: article - Mat Yasin, Nik Muhammad Faisal; Alias, Azil Bahari (2018)
Every process produces byproduct, byproduct can be dangerous or not. Hydrogen sulfide is one of the dangerous byproduct produced. In order to prevent hydrogen sulfide to harm workers or residents, control system is required. Currently, all industry has a control system such as adsorption system, to control dangerous component such as hydrogen sulfide. In order to optimize adsorption system, research is required. Researching using laboratory method is very dangerous due to nature of hydrogen sulfide. Thus isotherm and kinetic model is used as alternative method, as it doesn’t involve researching in laboratory. Each isotherm model and kinetic model equation has different uses for adsorption process. The isotherm models used are Langmuir, Freundlich and Elovich, while kinetic models used are Pseudo-First Order and Pseudo-Second Order. The main objective of this experiment is to find the most suitable equation for adsorption of hydrogen sulfide. Suitability of equation is determined by correlation coefficient (R²). The higher correlation coefficient, the more suitable the equation is to process. After result obtained, the most suitable isotherm and kinetic model are Elovich model and Pseudo-Second Order model respectively. R² for Elovich model is 0.9686 while R² for Pseudo-Second Order model is 0.9284. By comparing R² of each model, it is shown that Elovich and Pseudo-Second Order model are the most suitable for this adsorption process due to highest correlation coefficient.